PENGARUH PENANAMAN DISIPLIN TERHADAP KREATIVITAS ANAK USIA PRASEKOLAH DI TK. NURUL YAQIN NYALABU LAOK KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN TAHUN AJARAN 2021/2022 - Musyarrofatul Jannah; Wahono Wahono; Naili Sa’ida (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the effect of instilling discipline on the creativity of preschool children in kindergarten. Nurul Yaqin Nyalabu Laok, Pamekasan District, Pamekasan Regency, 2021/2022 Academic Year. Discipline is a way to build children so they can develop self-control. By using discipline, children can get a limit to correct their wrong behavior. The research method used in this study uses quantitative methods. With data collection techniques by observation, interviews, documentation. Analysis of the data used is a quantitative analysis because the data obtained can be realized in the form of numbers. The results obtained in this study are that there is an Influence of Discipline Planting on the Creativity of Preschool Age Children in Nurul Yaqin Nyalabu Laok Pamekasan Academic Year 2021/2022, this shows that if students are applied and instilled a disciplined attitude, it will also be embedded in attitudes and habits students to be more creative so that it will be embedded also in children's habits to increase creativity in addition to school also in the family environment. Keywords: Discipline; creativity; documentation; observation